Experimental research on the dynamic behaviors of the keyhole and molten pool in laser deep-penetration welding. (19th March 2018) - Zhang, Yi; Lin, Qida; Yin, Xuni; Li, Simeng; Deng, Jiquan
Abstract: Both the morphology and temperature are two important characteristics of the keyhole and the molten pool in laser deep-penetration welding. The modified 'sandwich' method was adopted to overcome the difficulty in obtaining inner information about the keyhole and the molten pool. Based on this method, experimental platforms were built for observing the variations in the surface morphology, the longitudinal keyhole profile and the internal temperature. The experimental results of three dynamic behaviors exbibit as follows. The key factor, which makes the pool width go into a quasi-steady state, lies in the balance between the vortex and the sideways flows around the keyhole. Experimental observation shows that the keyhole goes through three stages in laser welding: the rapid drilling stage, the slow drilling stage and the quasi-steady state. The time for achieving a relative fixed keyhole depth is close to the formation time of the maximum pool width. The internal temperatures inside the keyhole and the molten pool first experience a rapid increase, then a decrease and finally go into a quasi-steady state. Compared to that in the unstable stage, the liquid–metal uphill formed in the stable stage of laser welding has less influence on the internal temperature.